M dwarf stars in the b294 field from the VISTA Variables in the Vía Láctea (VVV). Issue 3 (1st February 2023) - Cruz, Patricia; Cortés-Contreras, Miriam; Solano, Enrique; Rodrigo, Carlos; Minniti, Dante; Alonso-García, Javier; Saito, Roberto K
ABSTRACT: M dwarf stars are the dominant stellar population in the Milky Way, and they are important for a wide variety of astrophysical topics. The Gaia mission has delivered a superb collection of data, nevertheless, ground-based photometric surveys are still needed to study faint objects. Therefore, the present work aims to identify and characterize M dwarf stars in the direction of the Galactic bulge using photometric data and with the help of Virtual Observatory tools. Using parallax measurements and proper motions from Gaia Data Release 3, in addition to different colour-cuts based on VISTA filters, we identify and characterize 7 925 M dwarf stars in the b294 field from the Vista Variables in the Vía Láctea (VVV) survey. We performed a spectral energy distribution fitting to obtain the effective temperature for all objects using photometric information available at Virtual Observatory archives. The objects in our sample have temperatures varying from 2800–3900 K. We also search for periodic signals in VVV light curves with up to 300 epochs, approximately. As a secondary outcome, we obtain periods for 82 M dwarfs by applying two methods: the Lomb–Scargle and Phase Dispersion Minimization methods, independently. These objects, with periods ranging from 0.14–34 d, are good candidates for future ground-based follow up. Our sample has increased significantly the number of known M dwarfs in the direction of the Galactic bulge and within 500 pc, showing the importance of ground-based photometric surveys in the near-infrared.